The Invitation to Treat and Mu`atah in Online Contracts (American Journal of Islam and Society, 2009)
When dealing with an offer, it is crucial to determine whether a “statement” amounts to an “offer” or a mere “invitation to treat.” Even though “offer” and “acceptance” are among the basic elements of any binding contract, both [English] common law and Islamic law have their own views on what constitutes an invitation to treat. This paper focuses on the invitation to treat and mu`atah as specified in Islamic law. The following points will be discussed: (1) how the invitation to treat can be considered a valid contract, although common law has ruled it invalid because a mere invitation to treat does not constitute an offer; (2) a comparison of their differences in the context of online or cyber transactions. Several Qur’anic verses, hadiths, and opinions from Muslim and non-Muslim scholars will be presented, and specific cases will be referenced; and (3) providing a better understanding of both principles and an analysis of some critical issues, especially with regard to the invitation to treat.